PENGEMBANGAN E-MODUL BERBASIS MODEL PEMBELAJARAN BLENDED LEARNING TIPE FLIPPED CLASSROOM UNTUK KELAS VIII SMP/MTS - Auzura, Ifni (Departemen Matematika, 2023)
Mathematics is considered difficult by junior high school students, as evidenced by their poor academic performance. Learning outcomes are influenced by several factors, among these factors is student learning interest. Using the right teaching materials can inspire students to engage in interesting and fun learning. This has an impact on their desire to learn. Observations carried out on Field Experience Practice (PPL) at SMP Negeri 7 Padang and interviews with educators revealed that the teaching materials used were not interesting and did not arouse students' interest in learning mathematics independently at school or at home, causing students to become more passive in mathematics. they. The purpose of this research is to develop teaching materials that attract students' self-learning interest through the use of a flipped classroom type blended learning model to improve student learning outcomes in class VIII SMP Negeri 7 Padang. This type of research is design and development research, using the Plomp development model which has three stages, namely preliminary research, development or prototyping, and evaluation. This research was conducted in class VIII SMP Negeri 7 Padang. In conclusion, this e-module meets all valid e-module eligibility criteria and all practical e-module practical criteria.Keywords– Development,Blended Learning,Flipped Classroom.